Alternating Additive Manufacturing and Forming - An Innovative Manufacturing Approach - Papke, Thomas; Hafenecker, Jan; Römisch, David; März, Raphaela; Hentschel, Oliver; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2023)
In this work, an innovative manufacturing approach that includes a fully linked and integrated manufacturing system consisting of a laser-based directed energy deposition (DED-LB/M) module and a forming press is presented. The alternating additive manufacturing (AM) process is based on a combination of a DED-LB/M process using a laser power of 600 W and a feed rate of 400 mm/min and a subsequent forming process, in which the structure is upset with a hydraulic press using a constant forming force of 500 kN in order to smooth the surface and influence the accuracy of the components. For the generation of a fundamental process understanding, a cuboid, basic shape was chosen as geometry for the investigations. The aim is to improve part properties by applying the process steps to generate part properties, which are superior to solely additive manufactured material. It is shown that the geometry of additive manufactured structures can be adapted, and the top surface can be smoothed due to the forming operation. The mean roughness value Rz decreases up to 50% after the forming operation. The hardness can be increased by work hardening. Of special interest is that the higher hardness can be kept up even though a further DED-LB/M process step and forming operation are applied to the additively manufactured and formed structure again. Finally, an analysis of the new manufacturing approach regarding its potential is give
Keywords: forming; additive manufacturing; DED-LB/M; process combination

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes, 2022)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.<br
Keywords: Mechanical joining; Clinching; Aluminum; Characterization methods; Process-structure-property relationships

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (IOP Conference Series, 2021)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95

Experimental and Numerical Analysis of Cold Formed Multi Pin Structures Using a Multi-Acting Tool Design - Römisch, David; Merklein, Marion (12th Tooling Conference and Exhibition Tooling 2022, 2022)
Intelligent material combinations for the production of multi-material systems as well as lightweight construction to save weight are becoming increasingly important in industrial applications. However, the joining process of dissimilar materials poses challenges to established joining processes due to different mechanical properties and chemical incompatibilities and lead to a need for new, versatile joining technologies. The use of cold extruded pins made from the sheet metal plane is the subject of current research due to the added potential for weight saving and the advantage of process-induced work hardening. To produce these pins and especially multi-pin structures, however, new tool concepts are needed. In the present work, a multi-acting tooling design is presented to produce a multi-pin array consisting of a 3x4 matrix by extrusion from the sheet metal plane. The tool allows the punches, the blank holder and the ejector to be controlled independently. The individual pins can be formed both simultaneously in one stroke and sequentially to control the formation of each pin individually. The numerical model utilised for designing the active parts of the tool is used to analyse the complex, resulting material flow and to gain insights into the pin forming. Furthermore, first experimental results of cold extruded multi-pin arrays are presented to obtain a basic scientific understanding of the influence of the tool on the process in combination with the numerical result
Keywords: Multi pin extrusion; Multi pin tool; Joining by forming; Mechanical joining

Experimental Study on Joining by Forming of HCT590X+Z and EN-AW 6014 Sheets Using Cold Extruded Pin Structures - Römisch, David; Kraus, Martin; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2021)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t(0) = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t(0) = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.
CRIS-Team WoS Importer:2021-04-30

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, Julian; Kleffel, Tobias; Römisch, David; Papke, Thomas; Merklein, Marion; Drummer, Dietmar (Applied Composite Materials, 2021)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Continuous fiber reinforced thermoplastics; Fiber orientation; Hybrid part; Joining; Organo sheet; Pin

Innovative mechanical joining processes in versatile process chains - potentials, applications and selection procedures - Lechner, Michael; Kappe, Fabian; Römisch, David; Rostek, Tim; Wituschek, Simon (Materials Research Proceedings, 2023)

Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, David; Kraus, Martin; Merklein, Marion (Sheet Metal 2021, 2021)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressin
Keywords: joining by forming; multi-metal-systems; pin forming; pin joining

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strengt
Keywords: pin-joining; alternative pin geometries; joining by forming; versatile joining process

Investigation of the Influence of Formed, Non-rotationally Symmetrical Pin Geometries and their Effect on the Joint Quality of Steel and Aluminum Sheets by Direct Pin Pressing - Römisch, David; Kraus, Martin; Merklein, Marion (AJP2021, 2021)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight construction technologies a current trend. For this reason, multi-material systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by using cold formed pin structures has shown to be a process with high potential for joining multi-material systems. These pin structures can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pin structures are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form fit joint. Usually, cylindrical pin structures are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pin structures as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X + Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut is a crucial influence on the joint strength [1], the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined in order to analyze the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension test
Keywords: pin joining; mechanical joining; joining by forming

Investigation on pin caulking as a versatile joining process - Römisch, David; Merklein, Marion (Materials Research Proceedings, 2023)

Investigation on the limp properties of formed foils for hydrogen applications - Wituschek, Simon; Römisch, David; Lechner, Michael; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2024)
The mass production of bipolar plates for electrolyzers and fuel cells is a central step towards the realization of efficient and cost-effective energy systems of the future. However, current production processes are reaching their limits and can hardly realize the quantities that will soon be demanded, nor can they scale up to the required volumes. Particularly for the handling of half-plates and bipolar plates, major challenges are to be expected, especially with regard to production rates. Existing handling systems have restricted scalability and precision. Therefore, new stacking technologies are necessary, which have to be adaptable to the mechanical properties of the components and maintain tight tolerances during stacking to ensure hydrogen sealing for safety and efficiency. An important property in the handling of the plates is their limpness, which is distinguished by instability of the components as well as plastic deformation at low forces and moments. Therefore, the limp behavior of the components must be analyzed. To investigate the limpness of foil components, a flowfield is first formed using a 1.4404 stainless steel foil with a sheet thickness of 0.075 mm. Subsequently, the workpieces are analyzed in terms of their limp properties by means of a 3-point bending test.<br

Investigation on the load-bearing capacity and joint formation of hybrid functional components joined by orbital forming - Hetzel, Andreas; Wituschek, Simon; Römisch, David; Sippel, Frank; Lechner, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part E-Journal of Process Mechanical Engineering, 2024)
Increasing material costs, decreasing availability, and ever-higher demands on environmental compatibility and complexity require new strategies in the development and production of functional components. Consequently, a combined approach from the areas of design, material science, and manufacturing is mandatory, in order to meet the requirements. Reducing the number of parts, using lightweight materials and applying hybrid components with a multimaterial mix are possible solutions. Nevertheless, conventional joining operations like welding or riveting are reaching their limits in terms of material utilization, load-bearing capacity as well as versatility of the process. Thus, innovative and versatile joining by forming operations and process combinations are focus of current research. In this context, the innovative process of orbital forming had been investigated as a joining by forming operation to manufacture load-adapted hybrid functional components. By tilting of one tool component during the process, a radial material flow is generated, allowing the crimping of the two joining partners. Nevertheless, the load-bearing capacity in axial direction could be identified as limiting factor for a possible application. Therefore, the aim of this investigation is the development of a fundamental process understanding on the influence of a novel geometrical adaption of the joint on the resulting load bearing capacity. The influence of varying geometrical proportions of the joint on the quality is evaluated, considering the form filling, the geometrical properties of the components as well as the maximum transmittable axial load. As joining partners, the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 2.0 mm are use

Joining by forming technologies: current solutions and future trends - Buffa, Gianluca; Fratini, Livan; La Commare, Umberto; Römisch, David; Wiesenmayer, Sebastian; Wituschek, Simon; Merklein, Marion (International Journal of Material Forming, 2022)
The progressively more demanding needs of emissions and costs reduction in the transportation industry are pushing engineers towards the use of increasingly lightweight structures. This goal can be achieved only if dissimilar and/or new materials, including polymers and composites, are joined together to create complex structures. Conventional fusion welding processes have often been proven inadequate to this task because of the high heat input reducing the joint mechanical properties or even making the joining process impossible. Joining by forming technologies take advantage on the plastic deformation to create sound joints out of even very dissimilar materials. Over the last 25 years, several new processes, with increasing potential in effectively joining virtually every structural material, have been invented and developed. In the paper, a comprehensive overview of the most utilized joining by forming processes is given. For each process, an analysis of the current research trends and hot topics is provided, highlighting strengths and weaknesses for industrial application
Keywords: Light alloy; Joining; Welding; Solid state; Clinching; Riveting

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences, 2022)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: joining of CFRT/metal; hybrid technology; mechanical properties; pin geometry; continuous fiber reinforced thermoplastics

Joining of CFRT-steel hybrid parts via hole-forming and subsequent pin caulking - Römisch, David; Popp, Julian; Drummer, Dietmar; Merklein, Marion (Production Engineering, 2021)
In times of increasing global warming, the awareness of the necessity for significant CO2 reduction is growing. Especially in the transport and aerospace sector, lightweight construction has potential to achieve emission reduction goals by reducing the overall vehicle weight. Thereby, adding lightweight fibre-reinforced composites to materials such as steel and aluminium is used to achieve weight savings. Furthermore, continuous-fibre-reinforced thermoplastics (CFRTs) begin to replace more traditional thermoset thermoplastics due to their easier bulk production and uncomplicated storage. Hybrid parts often consist of a CFRT and a higher strength metal component. Here, the joining process poses the main challenge, due to different chemical and physical properties of the components. In the current state of the art, riveted and bolted joints are commonly used, leading to increased weight due to auxiliary elements and requiring precise bolt holes often destroying load-bearing fibres. Joining with cold formed pin structures is an innovative and versatile joining process, which avoids the need for auxiliary elements. These pins are subsequently inserted in warm formed holes in the CFRT component and then caulked to create a form-fitting hybrid joint. To obtain a fundamental understanding of this joining process, hole-forming and pin-caulking, are investigated in this study. First, the hole-forming with IR-radiation is investigated with regard to suitable process parameters and resulting fibre morphology. The formed holes are consequently mechanically characterized. Second, the caulking-process is investigated by iteratively upsetting a pin and subsequently measuring the geometry. Based on these findings two different suitable caulking degrees are defined and samples for mechanical as well as microscopic investigations are manufactured. The created joints are first investigated via micro-sections and reflected light microscopy to identify possible damage in the CFRT component, which can result from the pin caulking process. Second, a mechanical characterisation under shear load as well as pin extraction loads normal to the sample surface is conducted and the normal load tests are compared with the bearing strength of CFRT samples.
CRIS-Team WoS Importer:2021-12-31

Join sheet Metal with cold-Extruded Pins - Römisch, David (Assembly, 2024)
Lightweight structures and multi-material assemblies are of great interest to the automotive industry. However, joining dissimilar materials poses a challenge. Conventional joining methods, such as welding, bonding, screwdriving and riveting, have limited effectiveness due to differences in stiffness, chemical compatibility and thermal expansion. A new mechanical joining method, using pin structures formed in one of the parts, has shown promise for assembling dissimilar materials.
CRIS-Team Scopus Importer:2024-12-13

Mechanical joining of high-strength multi-material systems - trends and innovations - Merklein, Marion; Jäckisch, Manuel; Kuball, Clara-Maria; Römisch, David; Wiesenmayer, Sebastian; Wituschek, Simon (Mechanics & Industry, 2023)

Non-destructive testing in versatile joining processes - Lechner, Michael; Borgert, Thomas; Busch, Matthias; Harms, Arnold; Holtkamp, Pia; Kappe, Fabian; Römisch, David; Wituschek, Simon (Sheet Metal 2025, 2025)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT’s application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysi
Keywords: Computed Tomography; Metrology; Mechanical Joining

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2022)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.<br

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Drummer, Dietmar; Fratini, Livan; Füssel, Uwe; Gude, Maik; Homberg, Werner; Martins, Paulo A. F.; Bobbert, Mathias; Lechner, Michael; Kupfer, Robert; et al. (Journal of Advanced Joining Processes, 2022)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fibre reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processe
Keywords: Mechanical Joining; Joining processes; Pin-Joining; Clinching; Self-piercing riveting; Versatility

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2022)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
CRIS-Team Scopus Importer:2022-11-04
Keywords: joining by forming; pin joining; robustness analysis; versatile joining process

Tailored material flow in pin-extrusion of sheet metal under varying material and geometric conditions for enhanced joining technology applications - Römisch, David; Kraus, Martin; Merklein, Marion (International Journal of Material Forming, 2025)
Pin structures extruded from the sheet metal plane have numerous industrial applications. For instance, they can be used in bulk microforming to solve handling difficulties or in joining technology to connect dissimilar materials to overcome challenges of different chemical, thermal and mechanical properties of materials. Due to the absence of material flow restrictions in the direction of the sheet metal plane, pin extrusion is affected by numerous process-, workpiece- and tool-related parameters, which have a huge impact on the material utilization and the obtainable pin geometry. Within the scope of this study, a combined numerical-experimental research approach is used to analyze the influence of the material and its condition on the achievable pin height and the occurrence of the mostly undesired funnel formation at high punch penetration depths. For this purpose, elastic-ideal plastic and elastic-real hardening model materials are first investigated numerically, which are subsequently validated and verified in experiments by using the materials Cu-OFE and DC04 on a laboratory scale. Based on the results, recommendations for the material selection and its properties are derived in order to maximize the material utilization. In addition, a pin joining process with locally modified extrusion conditions to increase the load-bearing capacity, especially under axial load, is being investigated with DP600 and AA 6014-T4. This process is a new type of two-stage mechanical joining process without an auxiliary joining element in which pin structures extruded from the sheet metal plane are used to join dissimilar materials in a subsequent step. In this work, test specimens are locally pre-punched before pin extrusion to create an enhanced pin geometry in order to achieve an improved undercut in the subsequent joining process. As a result, a new type of pin geometry was realized and investigated, which shows a significant increase of up to 82% in load-bearing capacity under axial load compared to the existing reference pin geometr
Keywords: Pin extrusion; Material flow; Pin-joining; Sheet metal

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers, 2022)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growt
Keywords: thermoplastic composite; clinching; joining; material behaviour; FEM; compaction